Predictors based on cuproptosis closely related to angiogenesis predict colorectal cancer recurrence - Li, Haoran; Zhang, Yingru; Feng, Yuanyuan; Hu, Xueqing; Bi, Ling; Zhu, Huirong; Wang, Yan (Frontiers in Oncology, 2024)
Up to one-third of colorectal cancer (CRC) patients experience recurrence after radical surgery, and it is still very difficult to assess and predict the risk of recurrence. Angiogenesis is the key factor of recurrence and metastasis of CRC, which is closely related to copper metabolism. The expression profiling by microarray from two datasets in GEO was selected for quality control, genome annotation, normalization, etc. The identified angiogenesis-derived and cuproptosis-related lncRNAs and clinical data were screened and used as predictors to construct a Cox regression model. We evaluated the stability of the model and drew the nomogram. The samples were divided into high-risk and low-risk groups according to the linear prediction of the model, and Kaplan-Meier survival analysis was performed. In this study, we established a model to predict the postoperative recurrence of colon cancer, which exhibits a high prediction accuracy. Furthermore, we validated the negative correlation between cuproptosis and angiogenesis in colorectal cancer cell lines and the expression of lncRNAs in vitro.